Accountability Complexities in Non-governmental Organisation: A Reflection of Practical Mechanisms for Instilling Accountability in Selected Tanzania's Non-governmental Organisations - Sikira, Richard (International Journal of Scientific Research and Management (IJSRM), 2021)
Non-governmental Organisations are key development partners who receive funds and other support from various stakeholders for supporting human development. Receiving funds and other supports require a well-established accountability framework to which most NGOs do not adhere. The downward and upward accountability phenomena seem overly complicated for NGOs to strike a balance as they have diverse and antagonistic interests. Given that scenario, it was imperative to examine how the existing mechanisms, influence the accountability of NGOs with the bias of ANSAF, UCS and HAWA. The study used Dar es Salaam as the case study employing the case study research design with a sample size of 30. Data were gathered through interviews and semi-structured questionnaires and analysed through content analysis for qualitative data. Quantitative data were analysed through simple descriptive statistics. This study aims to examine the mechanisms selected NGOs employ to instil accountability in Tanzania. The study found that the selected NGOs apply various accountability mechanisms, while the most used one is performance assessment based on a short-term basis, followed by disclosure of funding sources. The study concludes that upward and downward accountabilities are overly complex phenomena in actual practice. Thus, NGOs need a proper dedicated balance between the two.